Attention to global warming and the success of environmental initial coin offerings : empirical evidence (2020)
We analyze the effects of attention to global warming on the success of environmental initial coin offerings (ICOs) measured by the total funding amount raised in the actual ICOs and the long-term survival of the projects. Using a database featuring 324 environmental initial coin offerings between 2017 and 2019, we find that attention to global warming increases the total funding raised in an environmental ICO. Moreover, we find that environmental offerings that occur during periods of greater attention to global warming are significantly less likely to fail in the long term. Our results are consistent with the idea that investor attention as a market-discipline mechanism increases the likelihood of survival for environmental ICOs.